The role of coanalgesics in pain treatment - Olga Wysokińska; Justyna Żyga; Anna Małek; Karolina Zadrożna; Klara Iwaniszyn-Zapołoch (Kazimierz Wielki University, 2022)
Introduction Pain management plays an important role in many fields of medicine. The basis of treatment is pharmacotherapy with typical analgesics such as NSAIDs, paracetamol and opioids, nonetheless due to their inadequacy and numerous side effects, drugs from other groups that act as coanalgesics are increasingly being used. State of knowledge The analysis of the effectiveness and use of individual pharmaceuticals for the treatment of pain is possible based on knowledge of basic aspects of the formation and reception of pain stimuli. In the whole process of transmission of nociceptive stimuli, receptors, which are the point of action of most of the drugs discussed in this article, play a special role. Conclusions A number of studies have proven that coanalgesics treatment in patients suffering from postoperative pain make it possible to reduce the doses of opioids used, which is clearly associated with a reduction in the incidence of nausea, vomiting, intestinal peristalsis disorders, as well as infections in the postoperative period, and reduces the risk of complications and allows for a shorter period of hospitalization. Coanalgesics also have applications in the treatment of chronic and neuropathic pain, where typical analgesics often fail to produce satisfactory results.